Comparative analysis of medical glue and positioning hooks for preoperative localization of pulmonary nodules - Wang, Haowen; Deng, Min; Cheng, Dexin; Feng, Rui; Liu, Hanbo; Hu, Tingyang; Liu, Dongdong; Chen, Cheng; Zhu, Peilin; Shen, Jian (Frontiers in Oncology, 2024)
Background: Through preoperative localization, surgeons can easily locate GGNs and effectively control the extent of resection. So it is necessary to choose an appropriate puncture positioning method. The purpose is to evaluate the effectiveness and safety of medical glue and positioning hooks in the preoperative positioning of GGNs and to provide a reference for clinical selection. Methods: From March 30, 2020, to June 13, 2022, a total of 859 patients with a CT diagnosis of GGNrequiring surgical resection were included in our study. 21 patients who either opted out or couldn't undergo preoperative localization for various reasons were excluded. Additionally, 475 patients who underwent preoperative localization using medical glue and 363 patients who underwent preoperative localization through positioning hooks were also excluded. We conducted statistical analyses on the baseline data, success rates, complications, and pathological results of the remaining patients. The success rates, complication rates, and pathological results were compared between medical glue group and positioning hook group. Results: There was no statistically significant difference between the two groups of patients in terms of age, BMI, smoking history, location of the nodule, distance of the nodule from the pleura, or postoperative pathological results (P > 0.05). The success rate of medical glue and positioning hooks was 100%. The complication rates of medical glue and positioning hooks during single nodule positioning were 39.18% and 23.18%, respectively, which were significantly different (p < 0.001); the complication rates during multiple nodule positioning were 49.15% and 49.18%, respectively, with no statistically significant differences (p > 0.05). In addition, the method of positioning and the clinical characteristics of the patients were not found to be independent risk factors for the occurrence of complications. The detection rate of pulmonary nodules also showed some positive correlation with the spread of COVID-19 during the 2020-2022 period, when COVID-19 was prevalent. Conclusion: When positioning a single node, the safety of positioning hooks is greater than when positioning multiple nodes, the safety of medical glue and positioning hooks is comparable, and the appropriate positioning method should be chosen according to the individual situation of the patient.